The Influence of tourist attractions, price perceptions and location on desicion to visit - Monica Monica; Sinthon Siahaan (Panorama Nusantara, 2022)
This research purpose is to analyze the impact of tourist tttractions, price perceptions and location on decisions to visit Moja Museum Jakarta. In this study using multiple linear regression method. The population used in this study were all visitors at the Moja Museum Jakarta and the amount of samples used in this study were 100 respondents by using accidental sampling technique. The data is processed using the Validity Test and Reliability Test, then with the Classical Assumption Test, Multiple Regression Test and to determine the Hypothesis by using the F Test and t Test. The results of this study prove that partially the independent variables, namely tourist attractions, price perception and location have a positive and significant effect on the dependent variable, namely the decision to visit Moja Museum Jakarta. Furthermore, simultaneously the three independent variable have been proven to have a positive impact and have a significant effect on the decision to visit Moja Museum Jakarta.